Emerging 5G Multicarrier Chaotic Sequence Spread Spectrum Technology for Underwater Acoustic Communication - Wu Jinqiu; Qiao Gang; Kang Pengbin (Complexity)
Generalized frequency division multiplexing (GFDM) is a newly introduced technique for the wireless fifth-generation (5G) standard based on multicarrier filter bank theory, which has the advantage of flexibility in setting the number of subcarriers and subblocks. The application of GFDM in underwater acoustic (UWA) communication can take full advantage of the limited spectral resources, which is a prime limitation in UWA communication and will promote the development of UWA network technology. However, the multicarrier communication technique utilized in radio 5G communication offers difficulty in channel estimation, and the influence of a channel cannot be ignored especially in the UWA communication field. Therefore, GFDM cannot be implemented directly in UWA communication; to solve this problem, a system combining chaotic sequence spread spectrum technology with GFDM is proposed, which is a novel technique with high spectrum efficiency. Simulation and experimental results verified the effectiveness of the proposed system.